THE IMPACT OF THE EDUCATIONAL STRUCTURE OF HUMAN CAPITAL ON BUSINESS PERFORMANCE OF ENTERPRISES IN THE REPUBLIC OF SERBIA - Arsić, Ljiljana; Kocić, Milan; Dobričanin, Sanja (Economic Outlook, 2025)
The aim of this paper is to critically analyze and evaluate the impact of human capital education on the economic growth of enterprises in the Republic of Serbia, with a special focus on theoretical and empirical aspects of the relationship between investments in knowledge and organizational productivity. Starting from modern economic and managerial paradigms that treat human capital as one of the main carriers of competitive advantage, the paper problematizes the levels and structure of the labor force education in Serbia, as well as the degree of compliance between educational profiles and the requirements of the modern business environment. Methodologically, the research relies on the analysis of relevant literature, statistical data and results of previous studies, in order to identify key correlations between the educational level of employees and growth indicators at the level of individual enterprises. The obtained findings indicate a strong positive impact of continuous investment in education and professional development on innovation, efficiency and financial performance of enterprises. The conclusion points to the need for a systemic approach to human capital development, which implies more intensive cooperation between educational institutions, the state and the private sector in order to create a dynamic and flexible labor market, capable of responding to the challenges of the modern knowledge-based economy.
Keywords: education; human capital; enterprise; economic growth; економски раст